Optimization of visual comfort: Building openings - Lotfabadi, Pooya; Hancer, Polat (Elsevier, 2023)
The concepts of visual comfort and lighting quality are among key components of architectural design. Although the building industry shows significant signs of progress in this regard, frameworks aiming at the integration of comfort conditions remains one of the main points of contention. In recent years many studies have been carried out about the potential of window sizes to reduce energy consumption. However, the existing body of literature is lacking regarding various variables on visual comfort and consequently energy efficiency at the same time. Therefore, this research proposes a model to fill this gap in architectural regulations. Building on a genetic algorithm, the study develops and examines a novel multi-objective optimization model which can be adapted in the building design stage. The examined model leads to develop a standard strategy that can be used to evaluate visual comfort while maximizing energy performance in buildings with diverse functions and located in various climates. This model is formed from three main evaluation steps, which can be named project modeling according to the design stage, comfort assessment and evaluation, optimization and decision-making process. Therefore, based on the research limitation, window-to-wall ratio and types of glazing materials have been selected as optimization variables to examine the methodology. In this regard, the results show that the range between 20 and 50% can be considered acceptable in the examined office building located in Northern Cyprus. Although 20-40% clear glass makes an acceptable range of opening, the most preferred range is 30-50% of reflective glass, which proposes a bigger opening with the same amount of energy performance.
Keywords: Optimization method; Energy efficiency; Visual comfort; Window-to-wall ratio; Glazing materials